Radio Frequency Cell Site Engineering Made Easy - Faruque, Saleh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces Radio Frequency Cell Site Engineering to a broad audience. The author blends theory and practice to bring readers up-to-date in key concepts, underlying principles and practical applications of wireless communications. The presentation is designed to be easily accessible, minimizing mathematics and maximizing visuals.
Introduction -- RF Coverage Planning -- Choice of Multiple Access Technique -- Frequency Planning -- Traffic Engineering -- Cell Site Optimization.
Keywords: Telecommunication; Computer networks .; Electronics; Communications Engineering, Networks; Computer Communication Networks; Electronics and Microelectronics, Instrumentation